Diffusion–reaction model for the internal sulfate attack in concrete. (15th January 2016) - Campos, A.; López, C.M.; Aguado, A.
Highlights: A diffusion–reaction model is developed for the internal sulfate attack (ISA). The ISA is caused by the oxidation of the pyrrhotite into the aggregates. The model can predict the distribution and evolution of the volumetric deformations. The proposed model was applied in two real dams. Abstract: In the analysis of the behavior of concrete structures affected by expansive problems, it is often necessary to use kinetics models of the reactions involved to assess and predict the magnitude, distribution, and evolution over the time of expansion. In this study, a diffusion–reaction model is developed for the internal sulfate attack (ISA) problem due to the oxidation of the pyrrhotite into the aggregates. The model takes into account the kinetics of the pyrrhotite oxidation under the two main oxidizers and the oxygen transport in the concrete. The dependence of the water content of the concrete is included in the analysis, which affects the reaction kinetics and oxygen diffusion. The developed model is applied to two real dams affected by the ISA. The results obtained validate the model and demonstrate its potential for evaluating and predicting the behavior of structures affected by the ISA.